Efektivitas model pembelajaran two stay-two stray dan teams games tournament berbantuan macromedia flash terhadap kemampuan pemecahan masalah matematis siswa (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2020)
This research is motivated by the importance of applying learning models to students' mathematical problem solving abilities. This study aims to determine the effectiveness of learning Two Stay-Two Stray (TS-TS) and Teams Games Tournament (TGT) learning models assisted by Macromedia Flash on students' mathematical problem solving abilities. The population of this research is the eighth grade students of junior high school. The research sample uses TS-TS, TGT and conventional learning models. Data is used for evaluation in the form of description. Data analysis used tests of normality, homogeneity, one-way anova, scheffe ', and simple linear regression. Based on the research results obtained are (1) There is a difference in the ability to solve mathematical problems between TS-TS learning models assisted by Macromedia Flash, TGT learning models assisted by Macromedia Flash and conventional learning models. (2) Learning TS-TS assisted by Macromedia Flash is better than conventional learning. (3) TGT learning assisted by Macromedia Flash is better than conventional learning. (4) There is an active effect on students who use Macromedia Flash-assisted TS-TS learning. (5) There is an active effect on students using Macromedia Flash-assisted TGT learning. (6) The ability to solve mathematical problems of students who use TS-TS and TGT learning is assisted by Macromedia Flash completely individually and classically. It can be concluded that the TS-TS and TGT learning models assisted by Macromedia Flash are more effective for students' mathematical problem solving abilities.Keywords: Two Stay-Two Stray, Teams Games Tournament, Macromedia Flash, Mathematical Problem Solving Ability
Keywords: two stay-two stray; teams games tournament; macromedia flash; mathematical problem solving ability